2001
DOI: 10.1073/pnas.201257398
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics and the evolution of ultraviolet vision in vertebrates

Abstract: Despite the biological importance of UV vision, its molecular bases are not well understood. Here, we present evidence that UV vision in vertebrates is determined by eight specific amino acids in the UV pigments. Amino acid sequence analyses show that contemporary UV pigments inherited their UV sensitivities from the vertebrate ancestor by retaining most of these eight amino acids. In the avian lineage, the ancestral pigment lost UV sensitivity, but some descendants regained it by one amino acid change. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
228
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 148 publications
(244 citation statements)
references
References 37 publications
12
228
2
2
Order By: Relevance
“…Unlike M/LWS, significant insights into the tuning sites of SWS1 are not gained (Fig. S2C); there are no simple rules, although a previous study has shown that site-directed mutations cause wavelength shifts (28).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike M/LWS, significant insights into the tuning sites of SWS1 are not gained (Fig. S2C); there are no simple rules, although a previous study has shown that site-directed mutations cause wavelength shifts (28).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the interactions between the 11-cis-retinal and various amino acids, the max shifts caused by mutations in the opposite directions are often nonsymmetrical (22)(23)(24). Hence, to understand the evolutionary mechanism that has generated the various max s of rhodopsins in nature, we must analyze ''forward'' amino acid replacements that actually took place in specific lineages.…”
Section: Resultsmentioning
confidence: 99%
“…53 The non-extrapolated result at a RVS threshold of 120 eV is 2.93 eV. A QM/MM calculation with CC2/TZVPP employed for the QM part yielded 2.90 eV (Ref.…”
Section: Comparison To Experimentsmentioning
confidence: 99%